Evaluation of Five Shallot (Allium Cepa L.) Varieties For Resistance to Shallot Yellow Stripe Virus (SYSV) - Zulverdi, Yudhika Ankenkuala Ramadhana; Martosudiro, Mintarto; Choliq, Fery Abdul (Journal of Tropical Plant Protection, 2022)
Shallot Yellow Stripe Virus (SYSV) is one of the economically important viruses of shallot. The incidence of SYSV infection can reach 66%-100%. The high level of SYSV infection on shallot is also due to the lack of resistance varieties to SYSV. This study aimed to determine the resistance of five varieties of shallot and the effect of SYSV infection on shallot production. The study used a completely randomized experimental design (CRD) using five shallot varieties as the treatment with four replication for each treatment. The shallot varieties were Bauji, Thailand, Bima Brebes, Tuk tuk (V4), Trisula (V5), and control. Each experimental unit consisted of 10 plants. The evaluation results showed that the Tuk-tuk variety was categorized as resistant, the Trisula variety as tolerant, and the Bauji, Thailand, and Bima Brebes varieties were categorized as susceptible. The shallot growth and production indicate that SYSV infection causes interference in the plant development process.